Aging reduces glial uptake and promotes extracellular accumulation of Aβ from a lentiviral vector - Zhao, Wenjuan; Zhang, Jiguo; Davis, Elizabeth G.; Rebeck, G. William (Frontiers in Aging Neuroscience, 2014)
We used a lentiviral system for expressing secreted human Aβ in the brains of young and old APOE knock-in mice. This system allowed us to examine Aβ metabolism in vivo, and test the effects of both aging and APOE genotype, two of the strongest risk factors for Alzheimer’s disease. We injected the Aβ1-42 lentivirus into the motor cortex of young (two month old) and old (20-22 month old) APOE3 and APOE4 mice. After two weeks of lentiviral expression, we analyzed the pattern of Aβ accumulation, glial activation, and phosphor-tau. In young mice, Aβ accumulated mainly within neurons with no evidence of extracellular Aβ. Significantly higher levels of intraneuronal Aβ were observed in APOE4 mice compared to APOE3 mice. In old mice, APOE4 predisposed again to higher levels of Aβ accumulation, but the Aβ was mainly in extracellular spaces. In younger mice, we also observed Aβ in microglia but not astrocytes. The numbers of microglia containing Aβ were significantly higher in APOE3 mice compared to APOE4 mice, and were significantly lower in both genetic backgrounds with aging. The astrocytes in old mice were activated to a greater extent in the brain regions where Aβ was introduced, an effect that was again increased by the presence of APOE4. Finally, phospho-tau accumulated in the region of Aβ expression, with evidence of extracellular phospho-tau increasing with aging. These data suggest that APOE4 predisposes to less microglial clearance of Aβ, leading to more intraneuronal accumulation. In older brains, decreased clearance leads to more extracellular Aβ, and more downstream consequences relating to astrocyte activation and phospho-tau accumulation. We conclude that both aging and APOE genotype affect pathways related to Aβ metabolism by microglia.